Review : Exploration of Squalene from Natural Materials as its Potential in Health and Food Fields - Permadi, Adi; Wilson, Mutiara (Indonesian Journal of Chemical Engineering, 2024)
Squalene, a natural isoprenoid, plays a critical role in sterol biosynthesis and exhibits various health benefits, including antioxidant, anti-inflammatory, and antitumor properties. Found in sources such as shark liver oil, amaranth, olive oil, and microbial species, its demand has surged across pharmaceutical, cosmetic, and food industries. However, traditional extraction methods, predominantly from shark liver, raise sustainability concerns. This study explores alternative sources and production strategies, focusing on plant-based and microbial synthesis of squalene. Amaranth seeds and olive oil were highlighted as promising renewable sources due to their high squalene content. Advances in synthetic biology and metabolic engineering have enabled microbial platforms, such as genetically modified yeasts and microalgae, to produce pharmaceutical-grade squalene sustainably. Moreover, the development of innovative extraction techniques, such as supercritical CO₂ extraction, enhances yield and purity while minimizing environmental impact. The research further emphasizes squalene’s potential as a precursor for cholesterol, hormones, and vitamins, alongside its role in improving human health through applications in vaccines, cardiovascular protection, and cancer prevention. Future work should prioritize optimizing extraction methods, exploring untapped natural sources, and scaling microbial production to address the growing global demand sustainably.